Analisis Tren Prevalensi Bahan Berbahaya dan Resiliensi Kader dalam Program Pasar Pangan Aman Berbasis Komunitas di Cilacap - Agnes Dwi Safarina (Eruditio : Indonesia Journal of Food and Drug Safety, 2025)
Food safety issues in traditional markets remain a systemic challenge due to the illegal use of hazardous chemicals such as formaldehyde and textile dyes, particularly in coastal areas with extensive seafood distribution chains. This study aims to analyze the trends in hazardous substance prevalence and evaluate the effectiveness of the Community-Based Safe Food Market Program (PPABK) in Cilacap Regency, focusing on Tanjungsari Market. The methodology employed is a descriptive-analytical study design with a community intervention approach conducted from May to July 2025. Primary data were collected through incidental sampling (n=39) and tested using PPPOMN-verified rapid test kits. Research findings revealed a high pre-intervention prevalence of hazardous substances in the Cilacap region at 40.6%. During the intervention process, a detection paradox occurred, where prevalence increased from 16.7% to 40.0% due to the enhanced capacity of cadres in performing targeted sampling. However, in the final monitoring and evaluation phase, the prevalence significantly dropped to 0%. The study concludes that strengthening the resilience of market cadres as internal supervisors effectively changes trader behavior and creates independent oversight. The proposed policy recommendation is the replication of the PPABK model in other traditional markets, supported by the integration of local government budgets to ensure the sustainable availability of independent testing facilities.